Label-free identification carbapenem-resistant Escherichia coli based on surface-enhanced resonance Raman scattering. Issue 9 (26th January 2018) - Li, Jia; Wang, Chongwen; Kang, Haiquan; Shao, Liting; Hu, Lulu; Xiao, Rui; Wang, Shengqi; Gu, Bing
Abstract : In this study, a surface-enhanced resonance Raman scattering (SERRS) method has been developed for the accurate detection and identification of carbapenem-resistant and carbapenem-sensitive Escherichia coli . Abstract : In this study, a surface-enhanced resonance Raman scattering (SERRS) method has been developed for the accurate detection and identification of carbapenem-resistant and carbapenem-sensitive Escherichia coli . A total of 89 human isolates of Enterobacteriaceae, comprising 41 strains of carbapenem-sensitive E. coli (CSEC) and 48 strains of carbapenem-resistant E. coli (CREC), were tested to assess the feasibility of our proposed SERRS method as a clinical tool, and the results showed almost 100% accuracy.